Emotion regulation in substance use disorders: a systematic review and meta‐analysis. (11th August 2022) - Stellern, Jordan; Xiao, Ke Bin; Grennell, Erin; Sanches, Marcos; Gowin, Joshua L.; Sloan, Matthew E.
Abstract: Background and aims: The ability to regulate emotions effectively has been associated with resilience to psychopathology. Individuals with substance use disorders (SUDs) have been shown to have higher levels of negative emotionality, with some evidence suggesting impairment in emotion regulation compared with individuals without SUDs. However, no previous attempt has been made to systematically review the literature to assess the magnitude of this difference. We aimed to assess the association between SUD diagnosis and emotion regulation as measured by the Difficulties in Emotion Regulation Scale (DERS) and Emotion Regulation Questionnaire (ERQ) through a systematic review and meta‐analysis of existing findings. Methods: The systematic review was conducted using PubMed, PsycINFO and Embase. We examined cross‐sectional studies that compared a SUD group with a control group and measured emotion regulation using the DERS or the ERQ. The primary analysis focused on papers using the DERS, as this was the predominant instrument in the literature. Results: Twenty‐two studies met our primary analysis criteria, representing 1936 individuals with a SUD and 1567 controls. Individuals with SUDs relative to controls had significantly greater DERS scores, with a mean difference of 21.44 [95% confidence interval (CI) = 16.49–26.40, P  < 0.001] and Hedges' g =  1.05 (95% CI = 0.86–1.24, P  < 0.001). The difference was robust, remaining significant after removing outliers and studies with high risk of bias. Individuals with SUDs demonstrated poorer emotion regulation on each subscale of the DERS, with the largest deficits in the Strategies and Impulse subscales. The ERQ analysis revealed greater use of expressive suppression in those with SUDs relative to controls (Hedges' g  = 0.76, 95% CI = 0.25–1.28, P  = 0.004). Conclusions: People with substance use disorders appear to have greater difficulties in emotion regulation than people without substance use disorders.